Exploring links between visuospatial ability and anatomy learning in education: A bibliometric analysis and scientific mapping - Rahmani, Muhammad Z.; Bukhari, Agussalim; Wiyono, Nanang; Amru, Khaeriah; Baharuddin, Baharuddin; Nurhadi, Asty A. (Narra J, 2024)
The field of medical education faces a significant challenge in teaching human anatomy, a fundamental aspect of medical science that is often perceived as complex and demanding. Understanding the shapes and anatomical structure locations is crucial for students to master the intricacies of anatomy. Visuospatial ability, which involves comprehending three-dimensional structures and their spatial relationships, plays a pivotal role in anatomy learning. The aim of this study was to examine keywords, territories/countries, the number of publications, institutions, authors, and associated journals related to visuospatial ability in anatomy learning through extensive bibliometric analysis. Data were gathered from the Scopus database, and VOSviewer was employed to conduct a bibliometric analysis. Approximately 552 eligible articles were examined in their entirety. The findings indicated that the most significant research growth occurred in 2012, with the United States of America emerging as the leading country in the field.  Furthermore, Anatomical Science Education was recognized as the most esteemed journal in this field, with Wilson, T.D. being credited as the most influential author. The bibliometric data also demonstrated various approaches to improve visuospatial capacity in anatomy learning, such as utilizing virtual reality or other computer-assisted learning modalities and their integration into medical education practice. In conclusion, these findings highlight the critical role of visuospatial ability in facilitating the acquisition of anatomical knowledge and offer direction for future research in this area.